Análise e estudo de ETE's com sistema cíclico de lodos ativados e reator anaeróbio de leito fixo - Oliveira, Guilherme Feltrin de (Universidade Federal de São Carlos, 2023)
In the absence or low efficiency of domestic sewage treatment, the excess of carbonaceous organic matter and nutrients leads to pollution of water resources. To verify the treatment efficiency of the SANEJ and Potunduva Wastewater Treatment Plants, located in the county of Jaú (SP), the parameters measured for operational control in the influent and effluent sewage of the studied plants were analyzed in 2020 and 2021, which are: temperature, pH, DO, turbidity, BOD, COD, TSS, TDS, FSS, VSS, TSS, FSS, VSS, SDV, NT, N-Ammonia, nitrite, nitrate, total phosphorus, phosphate, total coliforms and E. coli. The obligation of domestic effluent treatment and consequently the improvement of water resources quality is legally foreseen, as described in CONAMA Resolutions 357/2005 and 430/2011; and in the state of São Paulo through Decree 8,468/1976. To comply with these laws, some of the parameters that compose them were evaluated in the second semester of 2021 and the first semester of 2022, which are: temperature, pH, turbidity, DO, BOD, TDS, NAmmonical, nitrite, nitrate, total phosphorus and E. coli. These parameters were analyzed upstream and downstream of the effluent discharge point into the receiving water body of the SANEJ and Potunduva Wastewater treatment plants (WWTPs), which have, respectively, the treatment types: CASS and RAALF. A comparison was made between both WWTPs to determine which one presented the highest treatment efficiencies. For BOD, the average efficiency results at SANEJ WWTP and Potunduva WWTP were, respectively, 93% and 94%, while for COD the average efficiency removal at SANEJ WWTP was 93% and 95% at Potunduva WWTP. Besides that, for the Ammoniacal Nitrogen the first WWTP showed an average efficiency removal of 68% and the second one of 74%. Concluding that the Potunduva WWTP has a higher efficiency in removing carbonaceous organic matter and nutrients, although the SANEJ WWTP has more parameters in compliance with the laws, due to its receiving water body being Class III, allowing higher concentrations of some parameters. Finally, some improvement points were suggested in this research, such as the insertion of a recirculation system of treated effluent in the Potunduva WWTP, in order to increase the efficiency of N-Ammonia removal.
Analysis and study of WWTP's with cyclic activated sludge system and fixed bed anaerobic-aerobic reactor
Keywords: Estação de tratamento de esgoto; Eficiência; Parâmetros; Legislações; Watewater treatment plant; Efficiency; Parameters; Laws; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS